دراسة الخصوبة المحتملة وعلاقات القياسات الشكلية والحيوية عند محار اللؤلؤ Pinctada radiata (Leach, 1814) في شاطئ مدينة اللاذقية - صقر, فائز; منصور, كاترين; حسن, نضال (Latakia University Journal -Biological Sciences Series, 2018)
The research dealt, for the first time, with studying the expectant fecundity of pearl oyster, Pinctada radiata in the coastal waters of Lattakia, which may serve as an introduction to its breeding and culturing. This research was achieved between June 2014 to May 2015 at Afamia region from Lattakia shore, monthly samples from littoral zone were collected (manually) and by using diving goggles from sublittoral zone to depth (3m). The number of studied Individuals were 205 Individual, the shell sizes varied between (19.2 – 65.8 mm) for height (SH), and between (20.1 – 57.7 mm) for Length (SL), and between (6.5 – 20.5 mm) for width or Thickness (SW), while the total weight (TW) (0.7235 – 27.3119 g), all the morphometric and biometric relationships were positive and solid. The results showed that the expectant fecundity of mature females (66 female) varied between (4.12 – 1.36 million egg), while spawning took place from June to the end of November, with peak during August and September. تناول البحث لأول مرة دراسة الخصوبة المحتملة عند محار اللؤلؤ Pinctada radiata في المياه الشاطئية لمدينة اللاذقية كمقدمة لتربيته واستزراعه. نفذ البحث خلال حزيران 2014 وحتى أيار 2015، في منطقة أفاميا من شاطئ مدينة اللاذقية، جمعت الأفراد بمعدل مرة واحدة شهرياً من المنطقة الشاطئية (يدوياً)، وباستخدام منظار الغوص من المنطقة تحت الشاطئية حتى عمق (3 متر). بلغ عدد الأفراد المدروسة 205 فرداً، تراوحت أبعاد الصدفة بين (65.8 – 19.2 مم) ارتفاعاً SH، وبين (57.7 – 20.1 مم) طولاً SL, وبين (20.5 – 6.5 مم) عرضاً أو ثخانةSW ، أما الوزن الكلي TW (27.3119 – 0.7235 غ)، وكانت جميع علاقات القياسات الحيوية والشكلية إيجابية وموثوقة. أظهرت النتائج أن قيمة الخصوبة المحتملة لدى الإناث الناضجة (66 أنثى) قد تراوحت بين (1.36 – 4.12 مليون بيضة)، أما وضع البيض فحدثت خلال الفترة الممتدة بين شهر حزيران ونهاية شهر تشرين الثاني، والذروة خلال شهري آب وأيلول.